FISCAL EFFECTIVENESS UNDER REGIONAL ECONOMIC INTEGRATION: INDONESIAN AGRICULTURAL PERFORMANCE CASE - Nasrudin Nasrudin; Bonar M Sinaga; Muhammad Firdaus; Dedi Walujadi (Economic Journal of Emerging Markets)
Abstract